An integrative review High-performance work systems, psychological capital and future time perspective - Abubakar, A. Mohammed; Foroutan, Taraneh; Megdadi, Khaled Jamal (Emerald Group Publishing Ltd, 2019)
Purpose Psychological capital (PsyCap) and future time perspective (FTP) are ambassadors of positivity among incumbent employees in organisations. However, remarkably little is known regarding the effectiveness of high-performance work systems (HPWS) in nurturing these constructs. The purpose of this study is to contribute and provide a complete frame of reference linking HPWS to PsyCap and FTP. Design/methodology/approach A synthesis analysis of existing literature was carried out to formulate managerial and practical propositions. Findings Drawing on the conservation of resources theory, affective events theory and Job Demands-Resources (JD-R) model, the present study proposes a research framework that links HPWS, FTP and PsyCap, with possible mediation effect of FTP in HPWS-PsyCap relationship and PsyCap in HPWS-FTP relationship. Practical implications - Although this paper did not test the model empirically, it offers important practical implications in terms of PsyCap and FTP perception development through HPWS practices. Originality/value A set of propositions that explain the relationships between the study variables is presented to enrich the understanding with organisation's HRM practices and its possible impact on employees.
Keywords: Resilience; Optimism; Self-efficacy; Hope; Future time perspective; Work practices